The first mitochondrial genome for the subfamily Asopinae (Heteroptera: Pentatomidae) and its phylogenetic implications - Qing Zhao; Jiufeng Wei; Wanqing Zhao; Bo Cai; Xin Du; Hufang Zhang (Mitochondrial DNA. Part B. Resources, 2017)
Here, we determined the complete mitogenome of Picromerus griseus, the first for the subfamily Asopinae. This mitochondrial genome contains 16,338 bp, with an A + T content of 71.69%, and contains 37 typical mitochondrial genes (13 protein-coding genes, 22 transfer RNA genes, two ribosomal RNA genes and a control region). The genome size, gene arrangement, A + T content, codon usage and secondary structures of 22 transfer RNA genes of the P. griseus mitogenome were similar to those of other sequenced pentatomoids. Bayesian analyses performed using the mitogenomes of P. griseus and its relatives, including 14 taxa, confirmed the reasonable placement of P. griseus.